A standby strategy model for an energy efficient soldering oven machine - Esfandyari, Alireza; Javied, Tallal; Reissmann, Felix; Franke, Jörg (2016 IEEE Conference on Technologies for Sustainability, SusTech 2016, 2017)
The convection based soldering technologies in electronics assembly consume massive electrical energy. The recent advancements in soldering technologies consume comparatively higher resources and need to be optimized for resource efficient production which is also the motivation for the present work. This paper has an energy consumption reduction perspective by considering a detailed analysis of operation and system component interactions with respect to various use phase regimes of the reflow oven in electronics manufacturing. The methodology derives a detailed analysis and monitoring of all electrical energy intensive components of the oven. The soldering process phase requires a state based modification of electrical energy consumption for non-productive process times. An optimization model enables to define the optimal state within a given waiting time window on energy-minimal operating state trajectories in the oven. Using the modelling framework, a strategic decision making processes that make it possible to exploit the potential for energy consumption minimization of any non-productive times is introduced.
CRIS-Team Scopus Importer:2023-03-07
Keywords: Electronics production; energy efficiency; soldering oven; standby mode